ANALISIS PELUANG EDUPRENEURSHIP DALAM MENINGKATKAN KESEJAHTERAAN GURU MI/SD - Nabila Hasna Utama; Shofiatul Kamaliah; Afila Firda Arifa; Afrisa Zayyana; Ferida Rahmawati (CV. Denasya Smart Publisher, 2025)
The welfare of Madrasah Ibtidaiyah (MI) and Elementary School (SD) teachers remains a crucial issue in educational development in Indonesia. Teachers serve not only as educators but also as individuals who are required to adapt to changing times, which demand creativity and innovation. One potential alternative is edupreneurship, an education-based entrepreneurship model that utilizes pedagogical competencies, technology, and local wisdom. This article aims to examine edupreneurship opportunities for MI/SD teachers as a strategy to improve their welfare, both economically and professionally. This research uses a literature review approach, analyzing relevant sources on the concept of edupreneurship and its implementation in education. The study's findings indicate that MI/SD teachers have opportunities to develop edupreneurship through various activities, such as creating innovative learning media, tutoring services, digital educational content, and developing locally valuable culturally-based products. Edupreneurship not only increases teachers' income but also expands their role as agents of change in society. Thus, edupreneurship can be a strategic solution to support the well-being and independence of elementary school (MI/SD) teachers in the modern era.